KONSISTENSI, AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN MASJID AL MARKAS AL-ISLAMI BERDASARKAN PSAK 109 - amir, adriani; Nuhung, Mahmud (Jurnal Ar-Ribh, 2018)
The study is aimed at the consisteny, accountability and transparancy of the financial management at Al-Markaz Al Islami Mosque based on PSAK 109, the type of research used in this study is quantitave descriptive research. Process Data is Data obtained from interviews and 2017 financial statements. Data collection technique usedin this study are documentation, field observations and interviews. Based on the result of this study it can be concluded that the Al-Markaz Al Islami Mousque has been open and responsible for managing mosque finance because according to them the financial statements made are a mandate from pilgrims who need to be managed properly. PSAK No. 109 has not been applied in presenting the current financial statements. Financial records are also still based on cash basis, namely recording transactions based on a cash in and cash out.